La producción de la subjetividad en los tiempos del neoliberalismo: hacia un imaginario con capacidad de transformación social - Rodríguez Victoriano, José Manuel (Cuadernos de Relaciones Laborales, 2003)
The neoliberal hegemony of the last few decades has brought with it immense economic, political and social transformation. The relative balance that had been established in western postwar societies in the dialectics between citizenship, subjectivity and social emancipation began to drastically change as of the early 1980s. (Santos 2000). The reorganisation of the capitalist system arising from this period has gelled, in social terms, in the increase of social vulnerability and social inequalities, and this has given rise to the emergence of the so-called ‘new social question’ (Robert Castel 1977). The territory of globalisation, the name that the current phase of capitalism has taken on (Etxezarreta 2001), is a totalising area of deregulation and privatisation. It is an area in which labour conditions become precarious along with other dimensions of citizens’ condition as well (Alonso 2000) including the reduction of political participation mechanisms to mere formal simulation and the autistic trivialisation of subjectivities and transforming identities (Benjamín 1997). The convergence of these dimensions points towards a new social, cultural, political and labour totalitarianism; a derivation towards what Boaventura de Sousa Santos (1999) defined as ‘new society fascism’. The thesis put forward in this article sustains that understanding new forms of inequality intrinsic in the present era of globalization requires an analysis of the neoliberal generation of human subjectivity from social and historical contexts. From a critical standpoint at the intersection between social and psychoanalytical theories (Castoriadis, Elliott, Guattari), this article analyses how the generation of subjectivity in neoliberalism reduces social players to individuals. Lastly, the article notes some reflections on the possibilities of an ideal able to bring about social transformation.